Evaluación de las propiedades fisicoquímicas del caucho seco y tiempo de coagulación del látex al implementar vinazas como coagulante (2022)
The present research work evaluated the physicochemical properties of dry rubber and the coagulation time of the natural latex of Mavalle S.A.S. and the coagulation time of the natural latex of the company Mavalle S.A.S. when coagulated with vinasse, coagulated with vinasse, which is a product of ethanol distillation from sugar cane. The process began in the laboratory, where different tests were carried out to establish 3 concentrations of stillage. different tests were carried out to establish 3 concentrations of stillage to coagulate the latex, and the physicochemical properties of the rubber were evaluated physicochemical properties of the dried rubber were evaluated after 2 days of maturation in the field at two drying temperatures drying temperatures, resulting in a decrease of Mooney Viscosity and plasticity when the sample was dried plasticity when drying the sample at high temperatures, a behavior opposite to the variation of the concentrations, since the concentrations, since as the concentration of stillage increases, plasticity and PRI increase. plasticity and PRI increase; Excel and Minitab were used to verify the results. Minitab were used to verify the results, in which the experimental design was presented. From the results obtained, it was possible to conclude that stillage can be a suitable substance for the coagulation of the suitable substance for latex coagulation, since it does not generate alterations in the material in the material. The results are within the parameters established by the ISO 2000:2014 standard the ISO 2000:2014 standard and the health effects are lower compared to formic acid.